Peran Kepatuhan Pelaporan Keuangan dan Kompetensi Aparatur dalam Mencegah Fraud Dana Desa: Studi Empiris di Kabupaten Sikka - Marselus Don Bosko; Tobias Joni Temu (Universitas Nusa Nipa Maumere, 2024)
This study aims to analyze the influence of financial reporting compliance and village officials’ competence on fraud prevention in village fund management in Sikka Regency. A quantitative approach with multiple linear regression analysis was employed. Data were collected through questionnaires involving 240 respondents, including village heads, secretaries, treasurers, and BPD members across 60 villages in 14 districts. The results show that both financial reporting compliance and officials’ competence have a positive and significant effect on fraud prevention. The adjusted R² value of 0.676 indicates that these two variables explain 67.6% of the variation in fraud prevention. These findings support the fraud diamond theory and highlight the importance of human resource capacity and reporting transparency in preventing financial misconduct in village governance. This study provides practical implications for local governments in strengthening accountable village fund management.